# If s(x) = x - 7 and t(x) = 4x^{2} + 3 which expression is equivalent to (ts)(x)?

**Solution:**

s(x) = x - 7

t(x) = 4x^{2} + 3

To find (ts) (x)

(t.s) (x) = (4x^{2} + 3) (x - 7)

By multiplying both the functions using the distributive property,

(t.s) (x) = 4x^{3} - 28x^{2} + 3x - 21

Therefore, (ts)(x) = 4x^{3} - 28x^{2} + 3x - 21

## If s(x) = x - 7 and t(x) = 4x^{2} + 3 which expression is equivalent to (ts)(x)?

**Summary:**

If s(x) = x - 7 and t(x) = 4x^{3} - 28x^{2} + 3x - 21

Math worksheets and

visual curriculum

visual curriculum